Influence of emotion on precision grip force control: A comparison of pleasant and neutral emotion - Bunno, Yoshibumi; Onigata, Chieko (Frontiers in Psychology, 2022)
The present study aimed to investigate the impact of emotion on force steadiness of isometric precision pinch grip that is not direction-specific. Thirty-two healthy volunteer subjects participated in the present study. Subjects were divided into two experimental groups: pleasant image group and neutral image group. The isometric precision pinch grip task was performed for three times. Specifically, the first task was performed before pleasant or neutral picture viewing, the second task was performed immediately after picture viewing, further the third task was performed 30 seconds after the second task. During the isometric precision pinch grip task, participants were asked to exert pinch grip force at 10% of maximal voluntary contraction with visual feedback. The coefficient of variation of force production and normalized root mean square value of electromyography activity were calculated. After pleasant picture viewing, coefficient of variation of pinch force production and normalized root mean square value of electromyography was decreased. While, in the neutral image condition, theses variables were not altered. More important, compared to the neutral image condition, pleasant emotion led to lower coefficient of variation of pinch grip force production. These findings indicate that pleasant emotion improves force control of isometric precision pinch grip. Therefore, in clinical settings, the emotional state of patients may affect the effectiveness of rehabilitation and should be taken into consideration.